Unveiling the impact of community knowledge in malaria programmes: A scoping review protocol. - Faizul Akmal Abdul Rahim; Mohd Hatta Abdul Mutalip; Ahmad Mohiddin Mohd Ngesom; Mohd Amierul Fikri Mahmud; Norzawati Yoep (PLoS ONE)
Background Despite significant reductions in recent malaria cases and deaths globally, the persistence of this health concern necessitates a shift from traditional top-down approaches. Consequently, malaria control initiatives increasingly focus on empowering local communities through community-centred strategies. Therefore, this scoping review protocol systematically explores diverse community knowledge approaches adopted in malaria programmes worldwide and their associated outcomes. Methods Adhering rigorously to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines, a comprehensive scoping review protocol was developed. Collaborating with a research librarian, a systematic search strategy targeted peer-reviewed literature from databases such as PubMed, Embase, Scopus, and Web of Science, complemented by a thorough grey literature search. Titles and abstracts will be screened, followed by extracting bibliographic details and outcome information using a standardized framework. Subsequently, the results will be systematically summarized and presented in a structured tabular format (S1 Checklist). Discussion This scoping review promises an in-depth understanding of current research regarding the impact of community knowledge in malaria programmes. The identification of knowledge gaps and intervention needs serves as a valuable resource for malaria-affected countries. The profound implications of community knowledge underscore its pivotal role in enhancing the effectiveness of prevention, control, and elimination efforts. Insights from this review will assist policymakers, empowering implementers and community leaders in designing effective interventions. This concerted effort aims to adeptly leverage community knowledge, thereby propelling progress toward the achievement of malaria elimination goals.